PASSWORD BASED CIRCUIT BREAKER USING ARDUINO - Prof. Shaikh N. F. (International Journal of Innovations in Engineering Research and Technology, 2023)
The password-based circuit breaker is a device that allows or denies access to an electrical circuit based on the input of a correct password. This project uses an Arduino R3 board, relay, keypad, LCD display, and breadboard to create a secure and reliable circuit breaker system. The user inputs the correct password via the keypad, and the circuit breaker is either enabled or disabled based on the validity of the password. The system provides visual feedback to the user through the LCD display, which shows the status of the circuit breaker and any errors or prompts. This password-based circuit breaker can be used in a variety of applications, such as securing valuable electronic equipment or protecting children from dangerous electrical devices. Overall, this project provides an effective and user-friendly solution for controlling access to electrical circuits.